PENGARUH PERMAINAN KERETA API GEOMETRI TERHADAP KEMAMPUAN GEOMETRI ANAK USIA 4-5 TAHUN DI TK PERTIWI DESA SELAT BARU KECAMATAN BANTAN KABUPATEN BENGKALIS - Pratiwi, Ellin Kartika; Indarto, Wusono; Febrialismanto, Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Based on the results of field observations on the ability of geometry’s students have not developed optimally. So it is necessary to implement the railway geometry game. This study aims to determine the effect of rail geometry game on ability of children aged 4-5 years in kindergarten Pertiwi Selat Baru, Bantan District Bengkalis regency. The sample used in this research were 15 students. The data collection techniques used are observation and documentation. Data analysis technique used t-test with SPSS 20. The research hypothesis is that rail geometry has influence game on geometric ability of age 4-5 years in kindergarten Pertiwi Selat Baru, Bantan District Bengkalis regency. It’s can be known from the analysis of data obtained t hitung =19,000 and Sig. (2-tailed) = 0.000. Because Sig. (2-tailed) = 0.000 <0,05 hence it can be concluded that there is difference of rail geometry ability of students significantly after rail geometry in learning. In Hypothesis test can be seen tct = 19,000> ttabel = 2,15. So it means Ho was rejected and Ha was accepted which means there is a very significant difference between before and after doing experiment with applying rail geometry. The influence of rail geometry game on geometric ability of children aged 4-5 years in kindergarten Pertiwi Selat Baru, Bantan District Bengkalis regency of 57.57%.Keywords: Game on Geometry Ability, Rail Geometry